Climate Change and Bangladesh: Geographical and Socio-economic Impacts - Jahan, Farjana; Quddusi, Kazi SM Khasrul Alam (Dhaulagiri Journal of Sociology and Anthropology, 2014)
Climate change, the effects of greenhouse effect and global warming, is out to alter the global map with its devouring prospects of sending a number of countries under the waves. Unfortunately yet unavoidably, Bangladesh stands at the forefront of climate forays. Its land, water and weather are being severely affected by undesirable climatic changes. Alarmingly, the dangers are to be intensified unless the trend is reversed. However, local initiative will hardly be enough to offset the grave concerns of unintended climatic changes in Bangladesh. The changes will also impact the socio-economic conditions of the country, putting the future of the nation on the line. Some ominous signs are already there for the concerned to respond with required amount of fervour. DOI: http://dx.doi.org/10.3126/dsaj.v7i0.10439 Dhaulagiri Journal of Sociology and Anthropology Vol. 7, 2013; 113-132